Food insecurity and its association with dietary diversity: A cross-sectional study in rural households in Jammu - Bhavna Langer; Rajiv Kumar Gupta; Rashmi Kumari; Richa Mahajan (Wolters Kluwer Medknow Publications, 2024)
Background: Food insecurity is a matter of public health concern as it is associated with adverse health outcomes particularly among vulnerable population. Accessibility and availability of nutritious and culturally appropriate food is paramount to achieve zero hunger. To assess the prevalence of household food insecurity, to estimate the household dietary diversity and its association with household food insecurity. Material and Methods: Using multistage sampling 381 rural households were surveyed. Household Food Insecurity Access Scale and House hold Dietary Diversity Scale were used as study instruments. Chi square test was used to compare the two groups and P < 0.05 was considered to be statistically significant. Results: Prevalence of household insecurity was 33.3% (127) among the surveyed households and 8.1% (31) had severe food insecurity. The mean HFIS score was 6.85 ± 4.82. The household Dietary diversity score was 8.14 ± 1.54 for food secure and 6.51 ± 1.38 for severely food insecure households. There was a statistically significant difference in intake of milk and milk products, fruits, eggs and meat/poultry among food secure and insecure households (P < 0.001 respectively). Conclusion: Food insecurity was high in rural households and was associated with lower dietary intake of foods from protein group, necessitating a need to reinforce the food security programmes in rural India with focus to enhance protein rich diet.